Investigation of the factors that influence the smartphone purchase intention among Saudis in Malaysia - Alyami, Mona Majed M. (Kulliyyah of Information and Communcation Technology, International Islamic University Malaysia, 2016)
Smartphone penetration in Saudi Arabia is one of highest penetration rates in the world with 53 million of cell phone users in 2013. Therefore, the core aim of the current research is to examine the buying intent of smartphones by users in Saudi. Depending on the TAM prototype and recent developments in the literature, the analysis investigates the role of Perceived Ease of Use (PEU), Perceived Usefulness (PU), Social Influence (SI) Product Feature (PF), Brand Name (BN), Product Price (PP) and Dependency (Dep) on the Purchase Intention (PI) of smartphone among Saudi users who live in Malaysia. The set of data is collected through online questionnaire, and proper random sampling method that resulted in total respondents of 247 Saudis. Multiple regression assessment was performed to investigate the association amongst the study variables. According to the inferences drawn there is an association amongst all independent variables with purchasing decision significantly except Product Price (PP), which showed that only Perceived Ease of Use (PEU), Perceived Usefulness (PU), Social Influence (SI) Product Feature (PF), Brand Name (BN) and Dependency (Dep) influence the smartphone purchase intention among Saudis in Malaysia. The study adds to the current literature that lacks previous studies that conducted among Saudi users. The study also has important implications to smartphone providers.